Lipoprotein(a) and Blood Monocytes as Factors for Progression of Carotid Atherosclerosis in Patients with Premature Coronary Heart Disease - Alexandra V. Tyurina; Olga I. Afanasieva; Marat V. Ezhov; Elena A. Klesareva; Tatiana V. Balakhonova; Sergei N. Pokrovsky (Diseases)
Background. Elevated lipoprotein(a) [Lp(a)] levels are a key factor in the early formation and progression of atherosclerosis. Monocytes in individuals with an elevated Lp(a) level are represented by an activated inflammatory phenotype and have an increased ability for transendothelial migration. This work studies the association between Lp(a), monocytes, and the progression of carotid atherosclerosis in patients with premature coronary heart disease (CHD). Methods. This study included 102 patients with CHD manifested before 55 in men and 60 in women who underwent two carotid duplex scans with an interval of 5 [3; 8] years. The criteria for the progression of carotid atherosclerosis were the appearance of new plaque and an increase in stenosis by >10% in any of the six segments. The lipid profile, Lp(a), and hematology with the calculation of the lymphocyte–monocyte ratio (LMR) were determined in all the patients. Results. The median blood monocyte count was 0.54 × 109/L, and the median LMR was 4.18. In 70 patients, we revealed the criteria for carotid atherosclerosis progression. The groups did not differ by demographics, risk factors, or the blood lipid and lipoprotein levels, except for Lp(a); this concentration was higher in the patients with carotid atherosclerosis progression. The odds of atherosclerosis progression were highest in the patients with an elevated Lp(a) level and a blood monocyte count above the median (16.8, 3.4–83.0, p < 0.001). Carotid atherosclerosis progression was associated with LMR < 4.18 and an elevated Lp(a) level (OR = 4.3, 1.1–17.2, p = 0.04) and not associated with the patients with Lp(a) levels < 30 mg/dL and an LMR above the median. Conclusions. An elevated Lp(a) level and monocyte count provide the highest probability of the progression of carotid atherosclerosis in patients with premature CHD.